Public budgeting systems - Lee, Robert D. (Burlington, MA Jones & Bartlett Learning, 2013)
Now in its Ninth Edition, Public Budgeting Systems is a complete and balanced reference that surveys the current state of budgeting throughout all levels of the United States government. The text emphasizes methods by which financial decisions are reached within a system as well as ways in which different types of information are used in budgetary decision-making. It also stresses the use of program information, since, for decades, budget reforms have sought to introduce greater program considerations into financial decisions. The Ninth Edition has been updated to give particular attention to several recent developments in public budgeting and finance including: ? Steps that have been taken by governments to battle the effects of the ?Great Recession? and to enhance economic recovery. In the US, this includes the actions of the Federal Reserve as well as legislative efforts, such as the American Recovery and Reinvestment Act. ? Significant increase in use of fiscal policy tools to stimulate economic recovery, in contrast to most recent previous 20 year period. ? The federal government?s direct role in the operations of the private sector will be explored. The government has become a major stockholder and therefore has a financial stake in seeing that corporations succeed. ? Unprecedented federal deficits, as well as extreme budgetary challenges at the state and local level, including a discussion of causes and possible solutions. ? Other changes during the Obama presidency, including the passage of comprehensive health care reform and changes in the management agenda. ? Continued developments in financial and debt management, including additional GASB requirements and the effects of the recent economic contraction on the borrowing prospects for state and local governments. ? Additional recognition of the effects of the global economy, resulting in an increase in the pages devoted to discussing international examples.
Includes bibliographical references and index.
Keywords: Budget--United States